Good clinical, laboratory and manufacturing practices : techniques for the QA professional - Carson, P. A. (Phillip A.), 1944-; Dent, N. J. (Nigel J.); Royal Society of Chemistry (Great Britain) (Cambridge : Royal Society of Chemistry, 2007)
42